Postbuckling of thick FGM cylindrical panels with tangential edge constraints and temperature dependent properties - Tung, Hoang Van (Vietnam Journal of Mechanics, 2016)
This paper investigates postbuckling behavior of thick FGM cylindrical panels resting on elastic foundations and subjected to thermal, mechanical and thermomechanical loading conditions. Material properties are assumed to be temperature dependent, and graded in the thickness direction according to a simple power law distribution in terms of the volume fractions of constituents. Governing equations are based on higher order shear deformation shell theory incorporating von Karman-Donnell geometrical nonlinearity, initial geometrical imperfection, tangential edge constraints and Pasternak type elastic foundations. Approximate solutions are assumed to satisfy simply supported boundary conditions and Galerkin procedure is applied to derive expressions of buckling loads and load-deflection relations. In thermal postbuckling analysis, an iteration algorithm is employed to determine critical buckling temperatures and postbuckling temperature-deflection equilibrium paths. The separate and simultaneous effects of tangential edge restraints, elastic foundations and temperature dependence of material properties on the buckling and postbuckling responses of higher order shear deformable FGM cylindrical panels are analyzed and discussed.